30 [compact disc] - Adele, 1988- (Columbia Records, 2021)
The first new music from Adele since the release of her third studio album 25 in November 2015. The album is produced with former collaborators Greg Kurstin, Max Martin and Shellback and Tobias Jesso Jr., as well as new collaborators Inflo and Ludwig Goransson. Features the first single Easy on Me.